2020
DOI: 10.1039/d0em00063a
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of ferrous iron with clay mineral surfaces during sorption and subsequent oxidation

Abstract: Under anoxic conditions, clay minerals sorb dissolved Fe(ii) predominantly by forming surface precipitates, which transform into Fe(iii)-phases upon aeration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 72 publications
(109 reference statements)
2
12
0
1
Order By: Relevance
“…However, trace amounts of Fe sulfides do not appear to be the major sink of Fe(II), which is a consequence of reductive dissolution of the ample present Fe(III) oxides. This indicates that Fe(II) is most likely adsorbed/substituted back into clay minerals which can provide a large surface for Fe adsorption [57,58]. The relatively higher adsorption affinity for Fe(II) is probably due to slightly alkaline pH conditions in the aquifers, in such adsorption of Fe(II) to clay minerals is favored at pH above 6.0 [59].…”
Section: Speciation and Reactivity Of Fe-s-as Coupled Minerals In The Sediments Profilementioning
confidence: 99%
“…However, trace amounts of Fe sulfides do not appear to be the major sink of Fe(II), which is a consequence of reductive dissolution of the ample present Fe(III) oxides. This indicates that Fe(II) is most likely adsorbed/substituted back into clay minerals which can provide a large surface for Fe adsorption [57,58]. The relatively higher adsorption affinity for Fe(II) is probably due to slightly alkaline pH conditions in the aquifers, in such adsorption of Fe(II) to clay minerals is favored at pH above 6.0 [59].…”
Section: Speciation and Reactivity Of Fe-s-as Coupled Minerals In The Sediments Profilementioning
confidence: 99%
“…The characteristic bands of 3697, and 3620 cm −1 correspond to the stretching vibration of the hydroxyl groups (OH) of Si and Al, respectively, in the clay minerals. Meanwhile, the absorption peaks at 1637 cm −1 can be attributed to the C=O stretching vibration of the carboxyl group (-COO) [ 7 , 8 ]. The Si-O-Si band is observed at 1032 cm −1 as a result of the Si-O vibration.…”
Section: Resultsmentioning
confidence: 99%
“…Among the particulates, the metal-bearing particles were the most influential in the contaminated soil. These contaminants, containing a diverse form of toxic heavy metals, are associated with particles not heated up to melting temperatures, metal fragments and Fe oxide particles [ 7 , 8 ]. A number of previous studies have reported that contaminant emissions into the atmosphere on a regional scale could be related to wind direction and the size of particulates emitted by the smelter [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some oxidation even proceeds under anoxic conditions, as catalyzed by the sorbate, e.g. NOM (Daugherty et al, 2017) or phyllosilicates (Van Groeningen et al, 2020), or by microorganisms (Bryce et al, 2018).…”
Section: Feox Precipitation and Morphology Are Governed By Heterogene...mentioning
confidence: 99%